Investigation of the optical properties of Mg(OH)2 and MgO nanostructures obtained by microwave-assisted methods - Al-Gaashani, R.; Radiman, S.; Yarub, Al - Douri; Tabet, N.; Daud, A. R. (Elsevier B.V., 2013)
Link to publisher's homepage at www.elsevier.com/